Examining philosophy itself - Shan, Yafeng (Chichester : Malden, MA, USA : John Wiley & Sons, Ltd., 2023)
"One of the most distinctive features of philosophy is self-reflection. Philosophers are not only concerned with metaphysical, epistemological, conceptual, ethical, and aesthetic issues of things around us, they also pay serious attention to the nature, value, methods, and development of philosophy itself. This book examines some of the most important metaphilosophical issues: Is philosophy progressive? Are metaphysical claims meaningful? What is the aim of philosophy? Should analytic metaphysics be replaced by naturalised metaphysics? What is the prospect of a digital approach to philosophy of science? Can poetry play a substantial role in philosophy? Examining Philosophy Itself will be of interest to researchers and advanced students in philosophy"--
Includes index.
"First published as Metaphilosophy volume 53, nos. 2-3 (April 2022)."--ECIP T.p.
Keywords: Philosophy; Philosophy -- Criticism and interpretation; Science -- Philosophy